Simulation modeling and analysis - Law, Averill M. (McGraw-Hill Education, 2015)
Provides a comprehensive and technically correct treatment of all important aspects of a simulation study. This book strives to make this material understandable by the use of intuition and numerous figures, examples, and problems. It is equally well suited for use in university courses, simulation practice, and self-study.